TINJAUAN YURIDIS TENTANG PENGHINAAN LAMBANG NEGARA OLEH WARGA NEGARA INDONESIA - I Ketut Windia (Kerta Dyatmika, 2019)
ABSTRAK State symbols and symbols of the state are two terms that have the same meaning, there is no difference. The symbol of the state is one of the symbols of state sovereignty and honor, as well as the symbol of the identity of the existence of existence of nation and state. Any person who strikes, writes, draws, or damages the State Coat with the intention of tarnishing, humiliating or demeaning the honor of the State Coat shall be subject to a maximum imprisonment of five years or a fine of not more than Rp 500 million. The formulation of the problem in this research is how is the law of humiliation of the state symbol by Indonesian citizen and how is the mechanism of determination against defamation of state symbol by Indonesian citizen. This type of research is a normative legal research moving from the state symbol of Pancasila is something sacred, in the Law of the Republic of Indonesia Number 24 Year 2009 About Flag, Language, and State Symbol, And National Anthem. The flag, language, and symbol of the country, as well as the Indonesian national anthem are symbols of state sovereignty and honor, as well as symbols of the identity of existence of nation and state. This study uses an approach that examines the applicable legislation, legal theory, and can be the opinion of scholars related to the problems in this scientific paper is the result of the insult law of the state symbol by Indonesian citizens. The conclusion of this research is the effect of the insult law of the state symbol by the citizens of Indonesia is Article 154a of the Criminal Code (KUHP) "Whoever tarnished the flag of the Republic of Indonesia and the symbol of the Republic of Indonesia shall be punished with imprisonment of a maximum of four years or a criminal a fine of at most forty-five thousand rupiah. "Article 68 of Law Number 24 Year 2009 Concerning Flags, Languages ​​and State Symbols, as well as National Anthems Anyone who strikes, writes, draws or damages the State Coat for the purpose of tarnishing, , or undermine the honor of the State Symbol as referred to in Article 57 letter a, shall be liable to a maximum imprisonment of 5 (five) years or a maximum fine of Rp 500,000,000.00 (five hundred million rupiah). The mechanism of determination against defamation of the state symbol by Indonesian citizens is in the handling of defamation cases against the symbol of the state must prove mensrea (evil intent) of the perpetrator. This malicious intent is manifested by the intent or intent of the offender while committing an alleged offense against the state emblem. Investigators must be able to prove the existence of evil will (mensrea). This evil will be shown when a person commits an act of contempt for the State embleKeywords: Humiliation, Symbol of the Country, Indonesian Citizen